1998
DOI: 10.1086/515634
|View full text |Cite
|
Sign up to set email alerts
|

Use Caution with Serologic Testing for Helicobacter pylori Infection in Children

Abstract: Commercial serologic assays accurately detect adult Helicobacter pylori infection. Their use in children remains controversial. An ELISA to detect H. pylori IgG in children was developed and compared with three commercial assays. ELISA standardization was done with sera from all ages and validation was done with another cohort of sera with known H. pylori status. Three commercial serologic assays were subsequently compared against this pediatric ELISA at independent sites, at which 142 pediatric serum samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
126
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 28 publications
10
126
0
3
Order By: Relevance
“…In contrast to previous studies, 5,6 we did not find an association between iron deficiency and H pylori seropositivity. Serologic testing for H pylori in children lacks sensitivity and specificity 22 and does not distinguish between past and current infection; this may have led to misclassification of H pylori status and subsequent attenuation of the association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies, 5,6 we did not find an association between iron deficiency and H pylori seropositivity. Serologic testing for H pylori in children lacks sensitivity and specificity 22 and does not distinguish between past and current infection; this may have led to misclassification of H pylori status and subsequent attenuation of the association.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic testing in children often leads to false-positive and -negative results and does not distinguish between past and current infection. 22 These data raise the possibility that H pylori infection may contribute to global iron deficiency, but no large or populationbased studies have been conducted to evaluate the association between iron deficiency and active H pylori infection (ie, infection documented by breath and/or stool testing) among children. …”
mentioning
confidence: 99%
“…44,45 However, these results must be evaluated carefully, considering that the age of patients can influenced serology results, 28,29 because children's holdings of antibodies can be lower than for adults. [46][47][48] These data make it difficult to standardize serology tests at pediatric ages. The results were better than reported from younger children (81% were older than 10 years).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ELISA method is an easily-performed, low cost and available method, the existence of different antigens in commercial kits 44 can influence the accuracy of the method, 29 with it being possible for discord- ance between sensitivity and specificity to occur. 49,50 These data indicate that is necessary to choose a non-commercial antigen that it is specific for each country or region 48 and obtain validation of the method and the cutoff for the age and population being studied, due to differences in infection prevalence. 28,29 In summary, our result indicated that bacterial culture alone could not be used as the gold standard due to its low sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, when these kits were tested in Asian countries, the diagnostic accuracy was significantly lower (Leung et al, 1999;Miwa et al, 2000;Obata et al, 2003). These differences may be due to several reasons, such as strain heterogeneity in different geographic regions (Ohtsuka et al, 1997;Miwa et al, 2002); cross-reactivity with other intestinal pathogens, which vary in different parts of the world ; and varying immunological responses to H. pylori antigens in different patient populations (Khanna et al, 1998).…”
Section: Introductionmentioning
confidence: 99%